Numerical Analysis of General Trends in Single-Phase Natural Circulation in a 2D-Annular Loop - Gilles Desrayaud; Alberto Fichera (Science and Technology of Nuclear Installations)
The aim of this paper is to address fluid flow behavior of natural circulation in a 2D-annular loop filled with water. A two-dimensional, numerical analysis of natural convection in a 2D-annular closed-loop thermosyphon has been performed for various radius ratios from 1.2 to 2.0, the loop being heated at a constant flux over the bottom half and cooled at a constant temperature over the top half. It has been numerically shown that natural convection in a 2D-annular closed-loop thermosyphon is capable of showing pseudoconductive regime at pitchfork bifurcation, stationary convective regimes without and with recirculating regions occurring at the entrance of the exchangers, oscillatory convection at Hopf bifurcation and Lorenz-like chaotic flow. The complexity of the dynamic properties experimentally encountered in toroidal or rectangular loops is thus also found here.